PD-1/PD-L Axis in Neuroinflammation: New Insights - Manenti, Susanna; Orrico, Mario; Masciocchi, Stefano; Mandelli, Alessandra; Finardi, Annamaria; Furlan, Roberto (Frontiers in Neurology, 2022)
The approval of immune checkpoint inhibitors (ICIs) by the Food and Drug Administration (FDA) led to an improvement in the treatment of several types of cancer. The main targets of these drugs are cytotoxic T-lymphocyte antigen 4 (CTLA-4) and programmed cell death protein-1/programmed death-ligand 1 pathway (PD-1/PD-L1), which are important inhibitory molecules for the immune system. Besides being generally safer than common chemotherapy, the use of ICIs has been associated with several immune-related adverse effects (irAEs). Although rare, neurological adverse effects are reported within the irAEs in clinical trials, particularly in patients treated with anti-PD-1 antibodies or a combination of both anti-CTLA-4 and PD-1 drugs. The observations obtained from clinical trials suggest that the PD-1 axis may play a remarkable role in the regulation of neuroinflammation. Moreover, numerous studies in preclinical models have demonstrated the involvement of PD-1 in several neurological disorders. However, a comprehensive understanding of these cellular mechanisms remains elusive. Our review aims to summarize the most recent evidence concerning the regulation of neuroinflammation through PD-1/PD-L signaling, focusing on cell populations that are involved in this pathway.